How Selfish Contestants Use Endogenous Emotions to Increase Subjective Utilities. Issue 1 (2nd January 2020) - Park, Sung-Hoon; Shogren, Jason
Abstract : We study a two-player contest in which each egoistic player can choose to release his emotion information to the rival. Each player selects his emotion-parameter value to maximize his material payoffs and his effort level to maximize his subjective utility. There are different equilibria depending on the difference between the abilities of the players. The favorite reveals his envious emotion and the underdog his altruistic emotion in the equilibrium if the favorite's ability is moderately higher than that of the underdog. Our results suggest that the classic result of the favorite-as-follower does not occur in the equilibrium of the full game.